A lady awakened eaudiobook - Grant, Cecilia (Blackshear Family, 2012)
Newly widowed and desperate to protect her estate and beloved servants from her malevolent brother-in-law, Martha Russell conceives a daring plan. Or rather, a daring plan to conceive. After all, if she has an heir on the way, her future will be secured. Forsaking all she knows of propriety, Martha approaches her neighbor, a London exile with a wicked reputation, and offers a strictly business proposition: a month of illicit interludes . . . for a fee. Theophilus Mirkwood ought to be insulted. Should be appalled. But how can he resist this siren in widow's weeds, whose offer is simply too outrageously tempting to decline? Determined she'll get her money's worth, Theo endeavors to awaken this shamefully neglected beauty to the pleasures of the flesh—only to find her dead set against taking any enjoyment in the scandalous bargain. Surely she can't resist him forever. But could a lady's sweet surrender open their hearts to the most unexpected arrival of all . . . love?